Development of Arduino Uno-Based TCS3200 Color Sensor and Its Application on the Determination of Rhodamine B Level in Syrup - Muhammad Syukri Surbakti; Muhammad Farhan; Zakaria Zakaria; Muhammad Isa; Elly Sufriadi; Sagir Alva; Elin Yusibani; Leni Heliawati; Muhammad Iqhrammullah; Khairi Suhud (Indonesian Journal of Chemistry, 2022)
The use of the notorious synthetic dye, rhodamine B, in food and beverage products has been widely reported. This application urges the need to develop an analytical method that can provide reliable rhodamine B data with an easy operational technique. Therefore, this research is aimed to develop an Arduino Uno-based TCS3200 color sensor and study its application to determine rhodamine B levels in syrup. The design of the analytical instrument included TCS3200, an Arduino Uno microcomputer, an Integrated Development Environment (IDE) software, a black box container, and a 24 × 2 matrix display screen, where samples were prepared via absorption using wool thread. With a linear range of 1–20 mg/L, our proposed colorimetric sensor had recoveries of 96.25–110.3%, which was better compared to that was obtained from the UV-vis (81.8–100.6%) method. The detection and quantification limits of the sensor were 2.766 and 8.383 mg/L, respectively. The syrup samples used in this study were purchased from the local stores in Banda Aceh. Based on the proposed TCS3200 color sensor, the highest rhodamine B concentration from the syrup sample was 16.74 mg/L. The t-test analysis in this study revealed that the Rhodamine B levels quantified using the newly developed TCS3200 color sensor were not statistically or significantly different from the UV-Vis spectrophotometer method.